How to find the answer for 4sqrtx(2sqrtx+3sqrt7)4x(2x+37) and simplify it too?

1 Answer
Sep 26, 2017

8x+12sqrt7sqrtx8x+127x

Explanation:

First, we distribute parentheses/brackets using: x(y+z)=xy+xzx(y+z)=xy+xz

Therefore,
4sqrtx(2sqrtx+3sqrt7)4x(2x+37) is the same as 4sqrtx*2sqrtx+4sqrtx*3sqrt74x2x+4x37

4sqrtx*2sqrtx=8x4x2x=8x because sqrtx*sqrtx=xxx=x
So, you can just multiply the numbers: 4*2=842=8 and add the xx.

For 4sqrtx*3sqrt7,4x37, you take 4*3=1243=12 and you combine sqrtxx and sqrt77 together.
So, the equation on the right side would be 12sqrt7sqrtx127x.

Add both parts together:
8x+12sqrt7sqrtx8x+127x